Application of Learning Media Assisted with Wordwall Applications in Improving Mathematics Learning Results for Class VI Students UPT SPF SD Inpres Maccini 1/1 Makassar City - Andi Aryasti; Erna Ervianti; Randy Saputra Mahmud; Wahyudi Wahyudi (Edumaspul: Jurnal Pendidikan, 2024)
The aim of the classroom action research was to find out how to implement learning media assisted by the wordwall application in improving the mathematics learning outcomes of class VI students at UPT SPF SD Inpres Maccini I/1. The type of research used in this research is Classroom Action Research (PTK). The subjects in this research were all 27 class VI students and the class VI homeroom teacher. The data collection techniques used are observation, tests and documentation. Data analysis techniques by means of data reduction, data presentation and drawing conclusions and verification. The results of this research show that there is an increase in teacher activity in using learning media assisted by the wordwall application in cycle I reaching the adequate category (C) and in cycle II reaching the good category (B). The social studies learning outcomes of students in the first cycle were 42.42% or 11 students obtained an average score of 62.12 with sufficient qualifications (C) and experienced an increase in the second cycle of 81.81% or 27 students with an average score of 77.87. with good qualifications (B). It can be concluded that the problem based learning model assisted by the Wordwall application can improve student learning outcomes in Mathematics subjects.